2003
DOI: 10.2527/2003.8161473x
|View full text |Cite
|
Sign up to set email alerts
|

Chilling and cooking rate effects on some myofibrillar determinants of tenderness of beef

Abstract: Our objectives were to examine the effects of prerigor excision and rapid chilling vs. conventional carcass chilling of two muscles on proteolysis and tenderness during the postmortem storage, as well as the effects of fast and slow rates of cooking on myofibrillar characteristics and tenderness. The longissimus thoracis (LT) and triceps brachii (TB), long head muscles were removed 45 min after exsanguination from the left side of 12 carcasses and chilled in an ice bath to induce cold shortening (excised, rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 47 publications
(60 reference statements)
5
28
1
2
Order By: Relevance
“…The WBSF values from the present study (Table 1) were higher than many others reported in the literature (Shackelford et al, 1999;King et al, 2003). Both the lack of an aging period and the cooking method could have contributed to obtaining such high values.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The WBSF values from the present study (Table 1) were higher than many others reported in the literature (Shackelford et al, 1999;King et al, 2003). Both the lack of an aging period and the cooking method could have contributed to obtaining such high values.…”
Section: Discussioncontrasting
confidence: 66%
“…Both the lack of an aging period and the cooking method could have contributed to obtaining such high values. It has been demonstrated that chilling and cooking rates and the interaction between these factors can have dramatic effects on beef tenderness (King et al, 2003). Moreover, the highest WBSF values are usually obtained 24 h postmortem, and coincidentally that was the sampling point chosen in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…It is generally accepted that loss of liquids during meat cooking is due to heat-induced protein denaturation which causes less water to be entrapped within the protein structures held by capillary forces . In addition, fast heating was reported to cause severe myofibrillar shortening and decreased sarcomere length and this was associated to higher cooking loss (King et al, 2003). Recently, relations between heating rates, cooking losses and protein changes were more completely established on pork also at a secondary protein structure level by means of combined FT-IR spectroscopy and low-field NMR relaxometry, as higher water depletion induced by faster heating was found to lead to random structure and aggregated b,-sheet as well lower content of a-helical structures (Wu et al, 2007).…”
Section: Meat Texturementioning
confidence: 98%
“…The differences in the response of parameters used to estimate water holding capacity might be due to differences in the origins of the liquid lost in each process. During cooking, the lost liquid comes from constitutive water and from the fat melted during heating, so the difference between breeds is attenuated (Mandell et al, 1997;King et al, 2003). Losses due to thawing, however, come mainly from constitutive water and, because of the effect of genotype on muscle structure and, hence, its capacity to retain water, observed differences between genotypes in water loss are more pronounced.…”
Section: Carcass Qualitymentioning
confidence: 99%